2017
DOI: 10.1080/21641846.2017.1299077
|View full text |Cite
|
Sign up to set email alerts
|

Clinical criteria versus a possible research case definition in chronic fatigue syndrome/myalgic encephalomyelitis

Abstract: Background The Institute of Medicine (IOM) recently developed clinical criteria for what had been known as chronic fatigue syndrome (CFS). Given the broad nature of the clinical IOM criteria, there is a need for a research definition that would select a more homogenous and impaired group of patients than the IOM clinical criteria. At the present time, it is unclear what will serve as the research definition. Purpose The current study focused on a research definition which selected homebound individuals who m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Obtaining in-person physician diagnoses would have strengthened this study. In addition, some consider ME and CFS two distinct illness [18], whereas others have suggested that it might be difficult to separate these two illnesses [19,20,21]. If there are two illnesses, then collapsing groups would complicate interpretations of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining in-person physician diagnoses would have strengthened this study. In addition, some consider ME and CFS two distinct illness [18], whereas others have suggested that it might be difficult to separate these two illnesses [19,20,21]. If there are two illnesses, then collapsing groups would complicate interpretations of the results.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Jason et al ( 63 ) suggested the following classification system, those with just chronic fatigue of 6 or more months would be the broadest category (similar to the Oxford criteria), those who meet a ME/CFS clinical criteria would be represented by the IOM ( 6 ) criteria (with few exclusionary illnesses), and a purer ME criteria could be based either on the Canadian Consensus Criteria ( 3 ) or work of Ramsay ( 36 ). Sophisticated and methodologically sound research methods could also be used to select and operationalize criteria for a research case definition ( 22 , 31 , 32 , 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibromyalgia (FM) is a debilitating disorder characterized by low pain threshold and muscle tenderness accompanied by bowel abnormalities, sleep disturbances, depressive episodes, cognitive problems and chronic pain [1][2][3][4]. Despite commonly comorbid with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), a disease also showing a complex clinical pathophysiology [5][6][7][8][9][10][11], these syndromes have been classified by the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) with separate codes (M79.7 and R53.82 or G93.3 if post-viral, for FM and ME/CFS respectively) [12]. However, disease distinctions remain under debate [5].…”
Section: Introductionmentioning
confidence: 99%